Hadith of Al-Bukhari’s Narration about Zakat and Its Relevance with the Role of Zakat in Poverty Reduction in West Java - sabar (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
This article discusses the hadith about the narration of al-Bukhari about the zakat and its relevance to the role of zakat in poverty alleviation in West Java. This study was written by qualitative method with library study as its approach. The data source is a library publication. Data types are written narrations or documents contained in publication sources. Data collection techniques are carried out by tracking the sources of such publications. analysis techniques in the form of takhrÄ«j al-á¸¥adÄ«th application followed by shará¸¥ al-á¸¥adÄ«th, both al-turathÄ« and al-muâ€™Äá¹£ir. This article found that hadith of narration of Al-Bukhari about zakat associated with poverty from the findings can be revealed that hadith is considered relevant to the role of contemporary economic issues as associated with the role of zakat in poverty alleviation in west Java.